PERBANDINGAN METODE BAGIAN DAN METODE PROGRESIF TERHADAP HASIL BELAJAR LARI SPRINT - Zickry Maulana, - (2018)
The purpose of this study was to find out the comparison of part methods and progressive methods on learning outcomes of sprinting. The method used is a quasi-experimental method, population in class VII students of the 7th City Junior High School. The sampling technique of cluster sampling was 30 students, divided into 2 groups, group A and group B. Treatment given to group A used part method and group B treatment using the progressive method. Based on the results of calculations and data analysis both groups have an influence on learning outcomes. Evidenced by the results of hypothesis testing with a significance level of 0.05 group method part tcount = -3.1443 < ttable = 2.048 and the progressive method group tcount = -2.1586 < ttable = 2.048. The conclusions based on the average part method test better influence than the progressive method on learning outcomes of sprinting. ;---Tujuanpenelitianiniadalahuntukmengetahuiperbandinganmetodebagian dan metodeprogresifterhadaphasilbelajarlarisprint. Metode yang digunakanadalahmetode quasi eksperimen, populasi pada siswakelas VII SMP Negeri 7 Kota Bandung. Teknik pengambilansampelcluster samplingsebanyak 30 siswa, dibagimenjadi 2 kelompokyaitukelompok A dan kelompok B. Treatment yang diberikankepadakelompok A menggunakanmetodebagian dan treatmentkelompok B menggunakanmetodeprogresif. Berdasarkanhasilperhitungan dan analisis data keduakelompokmempunyaipengaruhterhadaphasilbelajar. Dibuktikandenganhasil uji hipotesisdengantarafsignifikansi 0,05 kelompokmetodebagianthitung = -3,1443 <ttabel = 2,048 dan kelompokmetodeprogresifthitung = -2,1586 <ttabel = 2,048. Simpulannyaberdasarkan uji rata-rata metodebagianlebihbaikpengaruhnyadari pada metodeprogresifterhadaphasilbelajarlarisprint.